Higher Education Transformation in Pakistan: Political and Economic Instability - Hayward, Fred (International Higher Education, 2009)
The 2002 creation of the Higher Education Commission, an autonomous body charged with reforming the failing higher education system in Pakistan, marked the start of six impressive years of growth and improvement to its university system. Enrollments increased, quality improved, tenure-track systems encouraged research and retention, and most universities supported the commission. Political and economic instability, beginning in early 2008, began to threaten these gains. Uncertainty, inflation, and budget cuts challenge the sustained growth in Pakistan's higher education system, and may even reverse progress.